The Role of Organizational Culture and Leadership Style in Enhancing Employee Performance, with Job Satisfaction as an Intervening Variable, at PT XYZ - Ayu Permata Sari (Eduvest - Journal of Universal Studies, 2026)
The existence and sustainability of a business entity is fundamentally based on the quality of human resources which is the main driving force in every organizational activity. This study aims to determine the role of organizational culture and leadership style in improving employee performance, with job satisfaction as an intervening variable at PT XYZ. The research objective is the fashion footwear division of PT XYZ. Empirical data collection was conducted using a non-probability purposive sampling method with 300 respondents. Empirical data processing used SEM (Structural Equation Modeling) analysis techniques operated through the AMOS program. This study proposed seven (7) hypotheses, of which seven (7) were accepted. The findings of this study confirm that job satisfaction acts as a mediating bridge between organizational culture and leadership style in influencing staff performance. Statistically, both cultural factors and leadership have a significant impact on job satisfaction and employee output. Furthermore, the level of job satisfaction was found to contribute substantially and independently to the improvement of performance within the company.